Time Delay Systems Theory, Numerics, Applications, and Experiments - Insperger, Tamás; Ersal, Tulga; Orosz, Gábor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume collects contributions related to selected presentations from the 12th IFAC Workshop on Time Delay Systems, Ann Arbor, June 28-30, 2015. The included papers present novel techniques and new results of delayed dynamical systems. The topical spectrum covers control theory, numerical analysis, engineering and biological applications as well as experiments and case studies. The target audience primarily comprises research experts in the field of time delay systems, but the book may also be beneficial for graduate students alike. .
From the contents: Sampled-Data Stabilization of Nonlinear Delay Systems with a Compact Absorbing set and State Measurement -- Parametric Transfer Matrices for Sampled-Data Control Systems with Linear Continuous Periodic Process and Control Delay -- An SL/QP Algorithm for Minimizing the Spectral Abscissa of Time Delay Systems -- The Principle of "Borrowed Feedback" and Application to Control and Observation for Systems with Implicit State Dependent Delay -- A New Delay-Independent Stability Test for LTI Systems with Single Delay.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Dynamical systems; Control engineering; Multibody Systems and Mechanical Vibrations; Dynamical Systems; Control and Systems Theory